KINETICS ANALYSIS FOR ALUMINUM DISSOLUTION OF WEST KALIMANTAN BAUXITE THROUGH DIGESTION PROCESS - Des Amalia; M. Zaki Mubarok; Hisaini Husaini (Indonesian Mining Journal, 2014)
Kinetics model was developed for aluminum dissolution of West Kalimantan bauxite based on shrinking core model. A series of digestion tests was carried out to study aluminum dissolution from the ore sample with particles size distribution of 100% passing 60 mesh in 129 gpL of NaOH. The digestion tests were conducted at 140; 150 and 160°C under stirring speed of 500 rpm. The experimental result shows that after a certain period of diges- tion time, thus aluminum dissolution was fluctuated due to the formation of DSP as a result of the reaction of sodium aluminate solution with reactive silica in the ore. Aluminum dissolution data were analyzed and treated with Matlab software to predict time required for complete dissolution (t). By using the obtained t, hence fittings experimental data using 3 different rate-determining steps of kinetics models (i.e. interface reaction, film diffusion and diffusion through solid product layer) and dummy data were performed. Prediction of the rate-determining step of aluminum dissolution was then made by evaluating the value of square correlation coefficient (R2) from the regression equation of the models and then obtained the activation energy. The kinetics study which considers aluminum precipitation during digestion reveals that alumina dissolution mechanism is altered from interface chemical reaction with energy activation (Ea) of 29.57 kcal/mole to difussion through reaction product (ash) layer (Ea=2.77 kcal/mole).